The role of leadership in the process of remembering and forgetting: An experience report - Machado, Camila Alves; Lima, Ana Karine Girão; Pinheiro , Francisca Fernanda Alves; Oliveira, Patricia Santana de; Ibiapaba, Cleide Maria Carneiro da; Albuquerque, Elis de Souza; Reis , Virginia Angélica Silveira; Alves, Jamille Soares Moreira; Severino, Fernanda Gadelha; Lima, Afonso Carneiro (Seven Editora, 2023)
This research highlights the importance of preserving the collective memory of organizations to harness past experiences, lessons learned, and best practices, from the process of remembering and forgetting. It sought to answer the following question: what is the role of the process of remembering and forgetting in learning from the collective memory of managers, after changes in work processes through the pandemic. The general objective is to describe the observation of how social memory impacts the process of remembering and forgetting. The methodology applied is a social study, descriptive with the method of experience report, of the observations of the working group of managers for the remodeling of the work activities of the emergency care units located in Fortaleza-Ceará, and managed by the Institute of Health and Hospital Management. It is observed that memory management, from the process of remembering and forgetting, should be naturally practiced within the organization, to avoid wasting time, and financial resources, creating something that the unit already has. It is also concluded that the approaches reinforce the notions that organizational memory plays a crucial role in the creation of competitive advantage and the sustainability of organizations. DOI:https://doi.org/10.56238/alookdevelopv1-143